1986
DOI: 10.4319/lo.1986.31.3.0557
|View full text |Cite
|
Sign up to set email alerts
|

Light utilization efficiency and quantum yield of phytoplankton in a thermally stratified sea1

Abstract: Light utilization efficiency and quantum yield of phytoplankton in a thermally stratified temperate sea were evaluated. Underwater spectral irradiance was measured with a specially designed underwater irradiance meter and the specific absorption coefficient of phytoplankton was determined by a modified opal glass method. The light utilization efficiency of phytoplankton at each depth was derived from photosynthetically fixed energy divided by the energy penetrating into that depth, and quantum yield was estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
50
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 10 publications
12
50
0
Order By: Relevance
“…Both light utilization efficiency and quantum yield increased with depth and showed a maximum at the subsurface chlorophyll maximum in a lake and the sea (Priscu, 1984;Kishino et al, 1986). The same trends were found in this study, but both maxima were observed at the 10% light level except in the neritic area (Sta.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Both light utilization efficiency and quantum yield increased with depth and showed a maximum at the subsurface chlorophyll maximum in a lake and the sea (Priscu, 1984;Kishino et al, 1986). The same trends were found in this study, but both maxima were observed at the 10% light level except in the neritic area (Sta.…”
Section: Discussionsupporting
confidence: 73%
“…We used 0.016 m 2 ·µgChl.a -1 for the chlorophyll a-specific absorption coefficient for estimation of quantum yield independent of depth (Laws et al, 1990). We used it even though it has been reported that this value increased with depth due to differences in the energy spectrum of solar radiation with depth in natural water (Kishino et al, 1986;Laws et al, 1990). However, samples in our experiments were exposed to the same energy spectrum with different radiant intensity because of using the simulated in situ method.…”
Section: Light Utilization Efficiency and Quantum Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…PAR(z) is defined as Vandevelde et al 1989), and the latter is the maximal observable quantum yield (Kirk 1983;Kishino et al 1986). To run the model of Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Assuming light to be the dominant driver of vertical changes in primary production, we finally want to investigate vertical changes in phytoplankton light acclimation. Field (Grobbelaar 1985;Kishino et al 1986;MacIntyre et al 2002) and laboratory studies (Grobbelaar et al 1995;Mouget et al 1999) have previously shown a photoacclimative response to decreasing light by increasing the light utilization efficiency (a; slope of the initial part of the photosynthesis vs. light curve). Experimental studies (Staehr and Sand-Jensen 2006) have shown that a is higher under nutrient-replete conditions.…”
mentioning
confidence: 99%